Holocene relative shore-level changes and Stone Age palaeogeography of the Pärnu Bay area, eastern Baltic Sea. (January 2020) - Nirgi, Triine; Rosentau, Alar; Habicht, Hando-Laur; Hang, Tiit; Jonuks, Tõnno; Jõeleht, Argo; Kihno, Kersti; Kriiska, Aivar; Mustasaar, Mario; Risberg, Jan; Suuroja, Sten; Talviste, Peeter; et al.
The shore displacement and palaeogeography of the Pärnu Bay area, eastern Baltic Sea, during the Stone Age, were reconstructed using sedimentological and archaeological proxies and GIS-based landscape modelling. We discovered and studied buried palaeochannel sediments on the coastal lowland and in the shallow offshore of the Pärnu Bay and interpreted these data together with previously published shore displacement evidence. The reconstructed relative shore-level (RSL) curve is based on 78 radiocarbon dates from sediment sequences and archaeological sites in the Pärnu Bay area and reported here using the HOLSEA sea-level database format. The new RSL curve displays regressive water levels at −5.5 and −4 m a.s.l. before the Ancylus Lake and Litorina Sea transgressions, respectively. According to the curve, the total water-level rise during the Ancylus Lake transgression (10.7–10.2 cal. ka BP) was around 18 m, with the average rate of rise about 35 mm per annum, while during the Litorina Sea transgression (8.5–7.3 cal. ka BP), the water level rose around 14 m, with average rate of 12 mm per annum. During the short period around 7.8–7.6 cal. ka BP, the RSL rose in Pärnu, but probably also in Samsø (Denmark), Blekinge (Sweden) and Narva-Luga (NE Estonia–NW Russia), faster than the concurrent eustatic sea level calculated from the far-field sites. The palaeogeographic reconstructions show the settlement patterns of the coastal landscape since the Mesolithic and provide new perspective for looking Mesolithic hunter-fisher-gatherer settlement sites on the banks of the submerged ca. 9000 years old river channel in the bottom of the present-day Pärnu Bay.